Low Serum Nerve Growth Factor Levels Are Associated with Insulin Resistance, Beta Cell Dysfunction, and Neuropathy Screening Scores in Subjects with Type 2 Diabetes Mellitus - Dhini Sylvana; Dharma Lindarto; Santi Syafril (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Diabetic peripheral neuropathy (DPN) is a common complication of type 2 diabetes mellitus (T2DM), associated with chronic hyperglycemia, insulin resistance, and neuroinflammation. Despite the widespread use of Michigan Neuropathy Screening Instrument (MNSI) for early identification in neuropathy screening, studies assessing its relationship between NGF, insulin resistance, and neuropathy in T2DM patients, particularly in Indonesia, remain limited. Therefore, this study was conducted to evaluate associations between serum NGF, insulin resistance, β-cell function, and MNSI scores in T2DM.METHODS: Seventy-seven T2DM subjects were classified into DPN and non-DPN groups using MNSI. Subjects were excluded if they have comorbidities and conditions potentially affecting metabolic, immune, or organ function. Enzyme-linked immunosorbent assay (ELISA) was used for the measurement of serum NGF, enzymatic hexokinase method for fasting plasma glucose (FPG) and 2-hour postprandial glucose (2HPP), high-performance liquid chromatography (HPLC) for glycated hemoglobin (HbA1c), and chemiluminescent immunoassay for fasting insulin. Homeostatic model assessment of insulin resistance (HOMA-IR) and beta-cell function (HOMA-β) were then calculated.RESULTS: Most of the study subjects had NGF level of <11 pg/mL. NGF concentrations showed inverse correlations with HOMA-IR (r=–0.263, p=0.021) and HOMA-β (r=–0.316, p=0.005). In the DPN subgroup, NGF demonstrated a stronger negative correlation with HOMA-β (r=–0.425, p=0.009), whereas no significant correlation was found in non-DPN. HbA1c was higher in DPN (p=0.014). No significant associations were observed between NGF and HbA1c, FPG, or 2HPP. NGF was significantly associated with MNSI Part B scores (p=0.032), reflecting objective neuropathic findings, but not with MNSI Part A or total scores.CONCLUSION: Lower NGF levels were significantly associated with insulin resistance and β-cell dysfunction in T2DM. The association with MNSI part B suggests that physical examination findings may reflect NGF-related neuropathic alterations better than symptom-based assessments.KEYWORDS: diabetic peripheral neuropathy, HOMA-IR, HOMA-β, Michigan Neuropathy Screening Instrument, nerve growth factor, T2DM